Power system stability modelling, analysis and control - Sallam, Abdelhay A.; Malik, Om P. (The Institution of Engineering and Technology, 2015)
The following topics are dealt with: power system stability; synchronous machine; transformer modelling; transmission lines; power flow; transient stability; stability enhancement; series compensation; shunt compensation and compensation devices.